Beberapa Sumbangan Pemikiran Bagi Konsep "Rencana Pelestarian Situs Kedulan" - Sugeng Riyanto (Berkala Arkeologi, 2005)
The background for contributing ideas to the concept of the "Kedulan Site Conservation Plan" is partly based on the fact that this site is not only important for archaeologists or other academic circles, but to some extent also has important meaning for other circles, including the government, local communities, and society in a broad sense. Technically, the Kedulan (main) temple is already in the "ready to restore" stage after since 1993 intensively researched and carried out reconstruction efforts. Therefore, the proposal to preserve this site through a concept needs to be supported by many parties.